Study on energy retrofits for rural residential envelopes in Northwest China - Ping Liu; Miaomiao Li; Jiaolan Zhu; Weijie Yuan (Scientific Reports)
Abstract Rural dwellings in Northwest China are typically self-built, lack energy-saving measures, and suffer from high energy consumption and poor thermal performance. Retrofitting building envelopes is a key strategy to improve energy efficiency and reduce carbon emissions. However, most existing studies focus on single-factor retrofits and single-objective evaluations, limiting their comprehensiveness and practical application. This study addresses these gaps by investigating single- and multi-factor retrofit scenarios for a typical rural house in Dingxi City of Northwest China. Using orthogonal experiments and DeST-h simulations, optimal combinations of envelope elements were identified, and the entropy method was applied to evaluate energy savings, incremental costs, cost-effectiveness, payback periods, and carbon-emission reductions. The results of the case show that exterior wall insulation is the most effective single-factor retrofit, achieving energy-saving rates of 45.79–48.46%, while roof insulation and additional sunspaces yield over 20% energy savings. Multi-factor retrofits significantly outperform single-factor schemes, with energy-saving rates ranging from 46.84 to 70.47%. The optimal retrofit solution includes 70 mm EPS boards for exterior walls, 80 mm XPS boards for roof thermal insulation, a window-to-wall ratio of 20%, broken-bridge aluminum hollow windows (6 + 12A + 6), and insulated glass for the sunspace. This study contributes to integrating energy, economic, and environmental dimensions, addressing the limitations of previous single-objective methods by developing a comprehensive evaluation framework. It also provides region-specific retrofit solutions tailored for the climatic and socioeconomic conditions of Dingxi City in Northwest China. These findings offer practical guidance for policymakers and practitioners to enhance energy efficiency and promote sustainable rural housing development.